1972
DOI: 10.1111/j.1528-1157.1972.tb04543.x
|View full text |Cite
|
Sign up to set email alerts
|

A Medical and Social Survey of 231 Children with Seizures

Abstract: SUMMARY Two hundred and thirty‐one children with seizures, aged 0–17 years (131 males, 100 females), were followed for a few months up to 4 years. Most of them belonged to working class families living in poor housing. In 150 cases the seizures started in the first 5 years of life, whereas only 37 were below that age when first referred to us. This contrast is discussed and some useful conclusions are drawn with regard to the parents' attitude to the child's illness. A high incidence of seizures in near relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1
1

Year Published

1977
1977
2000
2000

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
0
6
1
1
Order By: Relevance
“…This is reflected in the distribution by seizure type, which is skewed toward the more unusual and more difficult to control types. Gregoriades (1972), reporting on a large series of children with seizures, found that 11% had classic absence seizures, whereas only 6% of our series did. Similarly, 50% had generalized tonic-clonic seizures (only), whereas 25% of our series did.…”
Section: Discussioncontrasting
confidence: 67%
“…This is reflected in the distribution by seizure type, which is skewed toward the more unusual and more difficult to control types. Gregoriades (1972), reporting on a large series of children with seizures, found that 11% had classic absence seizures, whereas only 6% of our series did. Similarly, 50% had generalized tonic-clonic seizures (only), whereas 25% of our series did.…”
Section: Discussioncontrasting
confidence: 67%
“…Many studies of cognitive function in children with epilepsy have shown that their mean test scores were below that of the particular test used (21)(22)(23) and that even children with epilepsy but with no known neurologic disorder obtained lower IQ scores (24,25). Although it has been reported that children with epilepsy might have normal IQs (26) or that their IQs were not significantly different from controls (27), neuropsychological defects are not rare in children with idiopathic epilepsy who have normal IQs (26,(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of this development has been variously reported as 1 % (Frantzen et al 1970), 3 % (van den Berg and Yerushalmy 1969), 11% (Taylor and Ounsted 1971), 16% (Degen and Goller 1967), 26% (Sogawa and lmamura 1972), and 57% (Livingston 1954). One-quarter (Gregoriades 1972) or 40% (Patrick and Levy 1924) of epileptic patients suffered from febrile convulsions in their early childhood.…”
Section: Introductionmentioning
confidence: 99%